Are free testosterone and cortisol concentrations associated with training motivation in elite male athletes? - Cook, C. J.; Crewther, B. T.; Kilduff, L. P. (Psychology of Sport and Exercise, 2013)
To examine correlative associations between salivary free testosterone (T) and cortisol (C) concentrations and training motivation in elite male athletes. Design Single group, longitudinal design with repeated measures. Methods Participants (n=15) completed a 5-week progressive resistance training programme. Across 2 weekly workouts, pre and post measures of salivary free T and C concentrations were taken along with voluntary chosen workload, as a proxy for training motivation. Strength and body mass were assessed pre and post training. Results Individual changes in pre-workout free T concentrations correlated strongly to voluntary workloads (pooled r=0.81, p<0.001). Pre-workout free C concentrations was weakly correlated to voluntary workload (pooled r=0.35). Pre-workout hormones (r=0.57-0.89) and the strength gains were also related. Conclusions The salivary free T concentrations of male athletes presented before training were strongly associated with subsequent voluntary workloads, indicating a potential link to training motivation.